Síntese, otimização e avaliação da atividade biológica de derivados de chalconas - Anjos, Murilo Machado dos (2015)
The world's population sees aging and some diseases that become more common. Alzheimer's disease (AD) is a dementia caused by loss of cognitive function of the individual and drugs used in their treatment is based on the inhibition of the enzyme acetylcholinesterase (AChE). Cancer is a group of diseases that develop due to the disorderly proliferation of cells may be related to genetic factors as well as dietary habits and exposure to radiation, the treatment being based on three main techniques: surgery, radiation and chemotherapy. In this work we synthesized 15 compounds (11 chalcones and 4 imines), based on the condensation of Claisen-Smth, and they are characterized by NMR (1H and 13C), IV These compounds were submitted to acetylcholinesterase activity by the modified method of Elman, using CCD and Martson, in addition to the evaluation of cytotoxic tumorias lines SF-295 (glioblastoma - human), HL-60 (acute leukemia promielítica) and HCT-116 (colon). The compounds showed no activity for the enzyme AChE front of the methods employed, and this cause investigated using molecular modeling methods, which sought in the literature active compounds for this enzyme, containing resemblance with the structures synthesized in this work. 80 descriptors were calculated being submitted to statistical analysis (Fisher's weight) where the number of variables is reduced to 24 and these have been selected GAP and bond angle where it was observed that the values of the synthesized compounds, mostly It was found out of range for the active compounds. The previous modeling studies are not sufficient to determine the causes of inactivity of the compounds, being necessary to the realization of a structure and reactivity studies. The evaluation of the antitumor compounds presented become more positive as the MCH-1